Effect of Promotion and Ease of Use on Customer Satisfaction and Loyalty on OVO Application Users - Anugrah, Fajar Tangguh (Quantitative Economics and Management Studies, 2020)
The development of a business that is currently globally quite rapid happening, this is related to the development of increasingly advanced technology, especially those based on the internet. Technological developments in Indonesia have also increased rapidly, one of which is changing daily activities is the payment system, where the circulation of cash is not as much as before. Non-cash payments are currently widely used by the public to transact, from debit card debit, e-money credit cards, and payment by applications through smartphones. With the emerging payment trend like that, many big companies are competing to create the same system, for example the largest network company in Indonesia, Telkomsel with its T-Cash, gojek by creating its Gopay and also recently emerged. with a promotional offer that interets Indonesian consumers is OVO. The purpose of this study was to analyze the effect of promotion and ease of use on customer satisfaction and loyalty. This type of research is quantitative. The study population was 100 respondents who used the OVO application in Surabaya. The analysis technique used is Partial Least Square (PLS). Data obtained from questionnaires and tested with the SmartPLS 3.0 application. The results of this study indicate that promotion and ease of use have a significant effect on customer satisfaction and customer loyalty. And customer satisfaction has a positive and significant impact on customer loyalty.